Вплив брендингу на мотивацію українських споживачів - Оксенюк, Катерина Ігорівна (Одеса : Гельветика, 2025)
Стаття присвячена дослідженню впливу брендингу на мотивацію українських споживачів. Обґрунтовано, що брендинг допомагає споживачам орієнтуватися в потоці інформації та швидко знаходити потрібні продукти. Ключовими факторами впливу брендингу на мотивацію українських споживачів є: якість та надійність; емоційний зв’язок; цінності та ідентичність; патріотизм; соціальний вплив. Доведено, що українські споживачі стають все більш вибагливими та обізнаними, і бренди повинні адаптуватися до їхніх потреб та цінностей. Споживачі звертають увагу не лише на продукт, але й на корпоративну відповідальність та місію бренду. Він впливає на їхню довіру, емоції та ідентичність. Ефективне використання брендингу допомагає підприємствам не лише привертати увагу споживачів, а й збільшувати їхню лояльність та зацікавленість у продуктах та по-слугах.

The article is devoted to a comprehensive study of the impact of branding on the motivation of Ukrainian consumers. It is established that branding has become an important factor that shapes consumer motivation and determines their attitude towards products and services. A brand creates an emotional connection with consumers. When a person experiences certain emotions when perceiving a brand, he becomes more motivated to purchase a product or use the brand’s service. It is branding that changes the perception of goods and services by consumers, increasing their value in the eyes of the target audience. It helps consumers navigate the flow of information and quickly find the products they need.The key factors influencing branding on the motivation of Ukrainian consumers are: quality and reliability; emotional connection; values and identity; patriotism; social impact.The role of branding in shaping consumer preferences was analyzed. The study showed that an effective branding strategy can significantly influence consumers, stimulating their motivation and changing their purchasing behavior. A brand gives consumers a sense of stability and reliability. If a brand has been around for a long time and has a positive reputation, consumers will trust its products and services. This encourages consumers to make purchases and increases their motivation to cooperate with the brand.It is proven that Ukrainian consumers are becoming more demanding and knowledgeable, and brands must adapt to their needs and values. Consumers pay attention not only to the product, but also to the corporate responsibility and mission of the brand. It affects their trust, emotions, and identity. Effective use of branding helps businesses not only attract consumer attention but also increase their loyalty and interest in products and services.Branding in Ukraine must take into account consider the emotional, national and social factors that influence consumer motivation. The importance of trust, transparency and social responsibility of brands is growing. Ukrainian consumers are becoming more demanding and knowledgeable, and brands must adapt to their needs and values.Branding is a powerful tool for stimulating consumer activity and building long-term relationships between brands and consumers. It helps consumers navigate the flow of information and quickly find the products they need. Successful brands not only offer quality goods or services but also build a strong emotional connection with their audience, becoming a part of their lives and identity.
The impact of branding the motivation of ukraine consumerd
Keywords: мотивація; бренд; брендинг; споживач; продукція; репутація; стратегія; споживча поведінка; позиціонування бренду